Data from "Growth capacity of an invasive cyanobacterium (Microcystis aeruginosa) on organic substrates in surface waters of permafrost peatlands" - Payandi-Rolland, D (via Mendeley Data) (2022)
This data set is related to a batch incubation of Microcystis aeruginosa on various aqueous organic substrates from permafrost peatlands. This experiment was set up to study this invasive cyanobacteria's potential growth on typical permafrost peatlands surface waters. THIS DATASET IS ARCHIVED AT DANS/EASY, BUT NOT ACCESSIBLE HERE. TO VIEW A LIST OF FILES AND ACCESS THE FILES IN THIS DATASET CLICK ON THE DOI-LINK ABOVE